Pengurangan Selip pada Jalan Tanah Angkutan Kayu Acacia Mangium - Yuniawati, Yuniawati (MECHANICAL ; Jurnal Ilmiah Teknik Mesin, 2015)
Slip as one of the obstacles that affect the smooth hauling of Acacia wood Mangium. This study aimed to determine the use of auxiliary tools and do not use auxiliary tools on the occurrence of slip on a dirt road transportation acacia mangium and its influence on the productivity of hauling, cost of production and damage to the soil. Methods research is design and make auxiliary tools, test, measurement and analysis of data in the form of slip calculation, productivity, cost of production and damage of soil. The results showed that the use of auxiliary tools from the holster wheel of iron chain crosses can minimize slip, increasing the productivity of timber transportation, minimize production costs and damage to the soil. Keywords: Slip, auxiliary tools, productivity, cost, damage of soil